The Effect of Oil on the Development of Education and the Social Status of Women in Kuwait 1946-1973 (⁎) - Ahmed, Zainab; Shekho , Tariq (Humanities Journal of University of Zakho, 2021)
In general, the oil topic is one of the topics that requires more attention and research because of being influential in all aspects of economic, social and political life. Therefore, we chose the topic of the effect of the effect of oil on the development of education and the social status of women in Kuwait 1946-1973.The country witnessed many changes during the discovery of oil and its export, then the revenues that contributed to reviving the Kuwaiti economy, which in turn contributed to the emergence of influences on the social reality. After it was exported in 1946 and ended in 1973, the year in which Arab countries used oil as a weapon against Western countries that sympathized with Israel in its war with Arab countries. In addition to the above, oil is an important natural resource for the social structure, including Kuwait. It is also one of the basic foundations of the state. The social development taking place in Kuwait was a result of the increase in oil revenues and its impact on the creation of new organizations, institutions and departments in Kuwait as educational institutions from schools and Kuwait University to sending many students through scholarships to abroad to study. Those components that changed many social perceptions towards Kuwaiti women who were living under the weight of customs and traditions that obscured their roles in society. The importance of studying the topic of oil and social transformations in Kuwait came because oil is one of the most valuable natural resources in the world. That is why some called it “black gold.” It might be better to describe it as the lifeline of most countries, as it is based on a large and diverse activity characterized by its complexity, and the breadth of its political, economic and social effects. The economic factor in most stages and cases is one of the most important factors and even the most dangerous impact on the economic and social conditions of any country in the world. From this standpoint, the study aims to explain the role of oil revenues in improving the economic conditions of Kuwait, which in turn contributed to the establishment of schools in its various stages and for both sexes, boys and girls, that have contributed to changing the thinking of social groups and their perception of the status of women and their roles in building the state and society. In light of the foregoing, a structure was developed for the study consisting of an introduction and three sections in addition to conclusions. We have devoted the introduction to the study of “discovering oil in Kuwait and increasing its revenues from 1946 to 1973,” while the first section is “aspects of social life in Kuwait 1946-1973.” As for the second section that deals with the study of "the role of oil in the emergence of educational institutions in Kuwait," and the third and final section deals with "the impact of oil in changing the reality of Kuwaiti women."